Progressive Dominant Hearing Loss (Autosomal Dominant Deafness‐41) and P2RX2 Gene Mutations: A Phenotype–Genotype Study. (8th October 2019) - Liu, Xue Zhong; Yan, Denise; Mittal, Rahul; Ballard, Megan E.; Feng, Yong
Abstract : Objectives/Hypothesis: P2RX2 encoding P2X purinoreceptor 2 has been identified as the gene responsible for autosomal dominant deafness‐41 (DFNA41) as well as mediating vulnerability to noise‐induced hearing loss (NIHL). The objective of this study was to investigate the audiological and molecular characteristics of P2RX2‐related deafness, with emphasis on its role in NIHL by determining the audiological characteristics of a previously reported six‐generation DFNA41 family with a 10‐year follow‐up. We have also summarized phenotype–genotype correlations of P2RX2‐related deafness in human and mouse models. Study Design: We describe clinical longitudinal follow‐up in the DFNA41 family with P2RX2 (p.Val60Leu) mutation and perform a systematic literature search in PubMed and poster presentations on meeting/conference websites to identify current insights into P2RX2‐mediated NIHL. Methods: Clinical and physical examinations of the family members were performed, and audiograms were obtained to assess the hearing thresholds. Clinical follow‐up features in this DFNA41 family are presented along with correlation analyses of phenotype–genotype in all reported families with P2RX2‐related deafness. Results: Progressive hearing impairment was confirmed by history and by audiological follow‐up testing in all the patients. The onset of hearing loss was between age 25 and 35 years. All affected subjects had bilateral sensorineural hearing loss involving all frequencies with some significant gender differences. Conclusions: Our study and the review of the literature suggest that P2RX2 plays a crucial role in predisposition to noise‐induced and age‐related hearing loss. A better knowledge about the P2RX2 ‐associated genetic variants can help in developing novel therapeutic strategies. Level of Evidence: 2b Laryngoscope, 130:1657–1663, 2020